Superconductivity in topological insulator β-PdBi2 under pressure. (25th January 2021) - Suzuki, Ai; Taguchi, Tomoya; Li, Huan; Wang, Yanan; Ishii, Hirofumi; Liao, Yen-Fa; Goto, Hidenori; Eguchi, Ritsuko; Kubozono, Yoshihiro
Abstract: The topological insulator PdBi2 exhibits two different crystal phases at ambient pressure, i.e., 'α-PdBi2 ' and ' -PdBi2 '. The pressure dependence of crystal structure and superconductivity of α-PdBi2 has been fully elucidated thus far. However, the physical properties of β-PdBi2 crystals under pressure have not been sufficiently investigated. In this study, we fully investigate the crystal structure and superconductivity of β-PdBi2 under pressure based on synchrotron x-ray diffraction (XRD) patterns. The temperature dependence of β-PdBi2 indicates its superconductivity with a superconducting transition temperature ( T c ) as high as 4.10 K, and its crystal structure is tetragonal [space group of I 4/ mmm (no. 139)]. The XRD patterns at 0–22.0 GPa indicate no structural phase transitions, and the unit cell volume shrinks monotonically with pressure, unlike the behavior of α-PdBi2 . Furthermore, α-PdBi2 transformed to β-PdBi2 under pressure. This suggests that β-PdBi2 is stable under pressure. The superconductivity is clearly observed at 0–11.8 GPa, and the value of T c is almost constant at ∼4.4 K. The temperature dependence of the upper critical field at ambient pressure and 10.7 GPa indicates that the superconductivity is not attributed to a simple s -wave dirty limit but an s -wave clean or p -wave polar model. This is the first systematic study of superconductivity of topological insulator β-PdBi2 under pressure.